2017
DOI: 10.1186/s13018-017-0622-z
|View full text |Cite
|
Sign up to set email alerts
|

Loading pattern of postoperative hallux valgus feet with and without transfer metatarsalgia: a case control study

Abstract: BackgroundPostoperative transfer metatarsalgia is a common complication after hallux valgus surgeries. Shortening of the first metatarsal is traditionally thought to be the primary cause of it. However, we speculate the abnormal loading pattern during gait is the real reason. This study is to determine specific differences in the loading patterns between reconstructive hallux valgus (HV) feet with and without postoperative transfer metatarsalgia, so as to find risky loading characteristics of this complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The loading ratio of the central rays increased up to 54.8% when the first metatarsal was shortened by 6 mm. This is close to the 55% that is thought to be a risky threshold based on previous studies (8).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The loading ratio of the central rays increased up to 54.8% when the first metatarsal was shortened by 6 mm. This is close to the 55% that is thought to be a risky threshold based on previous studies (8).…”
Section: Discussionsupporting
confidence: 85%
“…following the osteotomy procedure. In addition, the risk of metatarsalgia raises substantially when the central ray plantar loading ratio reaches 55% (8). Thus, when first metatarsal shortening reaches a certain extent (the central ray plantar loading ratio exceeds 55%), the distal end of the first metatarsal will be compensatively pushed down by 3 mm before being surgically fixed to the proximal part.…”
Section: Simulated First Metatarsal Shortening Proceduresmentioning
confidence: 99%
“…The basic biomechanical abnormality for transfer metatarsalgia is manifested as an alteration of forefoot loading pattern. A previous study by Geng et al [8] on post-osteotomy patients showed that the risk of metatarsalgia increased substantially when the plantar loading ratio of the central rays reached 55% in the push-off phase during gait. Therefore, this study focuses on the effect of magnitudes of the first metatarsal shortening on the plantar pressure distribution during push-off.…”
Section: Discussionmentioning
confidence: 99%
“…In order to validate its effectiveness, we also simulated the “pushing down motion” following the osteotomy procedure. In addition, the risk of metatarsalgia raises substantially when the central ray plantar loading ratio reaches 55% [8]. Thus, when first metatarsal shortening reaches a certain extent (the central ray plantar loading ratio exceeds 55%), the distal end of the first metatarsal will be compensatively pushed down by 3 mm before being surgically fixed to the proximal part.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation